Reconceptualizing risk: toward a theory of small risks in informal family play settings - Stamatis, Kristina M.; Jakopovic, Paula M.; Mendoza, K. Rende; Wisneski, Debora (Frontiers in Education, 2024)
Risk-taking in early childhood play is often associated with taking physical risks in outdoor settings. In this study, we explore the notion of “small risks” as a way to examine the how parents and children engage in intergenerational play at a series of informal, indoor pop-up play events that took place at community centers in a large, urban setting. We utilize auto-photography and small stories to examine participants’ self-selected examples of the ways their family units typically engaged in play. Our findings suggest that risk-taking in play, when re-envisioned through the lens of small risks, is more complex and nuanced than previously thought, particularly for families from non-dominant communities.